A Maize Mutant Impaired in SL Biosynthesis (zmccd8) Shows a Lower Growth, an Altered Response to Nitrogen Starvation, and a Potential Secondary Effect on Drought Tolerance - Laura Ravazzolo; Andrea Chichi; Franco Meggio; Leonardo Buzzicotti; Benedetto Ruperti; Serena Varotto; Mario Malagoli; Silvia Quaggiotti (Stresses)
Strigolactones (SLs) are essential phytohormones involved in plant development and interaction with the rhizosphere, regulating shoot branching, root architecture, and leaf senescence for nutrient reallocation. The Zea mays L. zmccd8 mutant, defective in SL biosynthesis, shows various architectural changes and reduced growth. This study investigates zmccd8 and wild-type (WT) maize plants under two nutritional treatments (N-shortage vs. N-provision as urea). Morphometric analysis, chlorophyll and anthocyanin indexes, drought-related parameters, and gene expression were measured at specific time points. The zmccd8 mutant displayed reduced growth, such as shorter stems, fewer leaves, and lower kernel yield, regardless of the nutritional regime, confirming the crucial role of SLs. Additionally, zmccd8 plants exhibited lower chlorophyll content, particularly under N-deprivation, indicating SL necessity for proper senescence and nutrient mobilization. Increased anthocyanin accumulation in zmccd8 under N-shortage suggested a stress mitigation attempt, unlike WT plants. Furthermore, zmccd8 plants showed signs of increased water stress, likely due to impaired stomatal regulation, highlighting SLs role in drought tolerance. Molecular analysis confirmed higher expression of SL biosynthesis genes in WT under N-shortage, while zmccd8 lacked this response. These findings underscore SL importance in maize growth, stress responses, and nutrient allocation, suggesting potential agricultural applications for enhancing crop resilience.